Postglacial species displacement in Triturus newts deduced from asymmetrically introgressed mitochondrial DNA and ecological niche models - Wielstra, Ben (BioMed Central, 2012)
BACKGROUND: If the geographical displacement of one species by another is accompanied by hybridization, mitochondrial DNA can introgress asymmetrically, from the outcompeted species into the invading species, over a large area. We explore this phenomenon using the two parapatric crested newt species, Triturus macedonicus and T. karelinii, distributed on the Balkan Peninsula in south-eastern Europe, as a model. RESULTS: We first delimit a ca. 54,000 km(2) area in which T. macedonicus contains T. karelinii mitochondrial DNA. This introgression zone bisects the range of T. karelinii, cutting off a T. karelinii enclave. The high similarity of introgressed mitochondrial DNA haplotypes with those found in T. karelinii suggests a recent transfer across the species boundary. We then use ecological niche modeling to explore habitat suitability of the location of the present day introgression zone under current, mid-Holocene and Last Glacial Maximum conditions. This area was inhospitable during the Last Glacial Maximum for both species, but would have been habitable at the mid-Holocene. Since the mid-Holocene, habitat suitability generally increased for T. macedonicus, whereas it decreased for T. karelinii. CONCLUSION: The presence of a T. karelinii enclave suggests that T. karelinii was the first to colonize the area where the present day introgression zone is positioned after the Last Glacial Maximum. Subsequently, we propose T. karelinii was outcompeted by T. macedonicus, which captured T. karelinii mitochondrial DNA via introgressive hybridization in the process. Ecological niche modeling suggests that this replacement was likely facilitated by a shift in climate since the mid-Holocene. We suggest that the northwestern part of the current introgression zone was probably never inhabited by T. karelinii itself, and that T. karelinii mitochondrial DNA spread there through T. macedonicus exclusively. Considering the spatial distribution of the introgressed mitochondrial DNA and the signal derived from ecological niche modeling, we do not favor the hypothesis that foreign mitochondrial DNA was pulled into the T. macedonicus range by natural selection.